Unpredictable Nanoparticle Retention in Commonly Used Plastic Syringes Introduces Dosage Uncertainties That May Compromise the Accuracy of Nanomedicine and Nanotoxicology Studies - Uwe Holzwarth; Unai Cossío; Jordi Llop; Jordi Llop; Wolfgang G. Kreyling (Frontiers Media S.A., 2019)
In recent animal experiments with suspensions of radiolabeled TiO2 nanoparticles large and highly variable radioactivity fractions were retained in disposable plastic syringes. After unloading between 10% and up to 70% of the loaded dose were still present in the syringes. As a consequence the effectively delivered nanoparticle dose to the animals was frequently much smaller than the nominal dose of the nanoparticles loaded into the syringe. The high variability of this nanoparticle retention challenges the application of a precise, predefined dose and creates a major error source when normalizing organ and tissue contents to the dose loaded into the syringe, which is usually set as the applied dose. A control study was performed employing six commonly used syringe types with seven types of radiolabeled oxide and metallic nanoparticles. For this purpose the syringes were loaded with a given volume of nanoparticle suspension, the radioactivity was measured, the syringe was unloaded and the activity measurement was repeated with the empty syringe. The highest retention values were found when using TiO2 nanoparticle suspensions with Tuberkulin type syringes. In the worst case between 6.6% and 79.1% of the nanoparticles were retained in the syringe. When using the same nanoparticle suspension with an insulin-type syringe the retention was reduced to 1.4% to 20.6%. For amorphous silica nanoparticles the maximum observed retention was 8% and for Au nanoparticles it was 5.1%. Further data gathered from in vivo animal imaging studies show that nanoparticle retention in syringes also affects experiments with nanoparticles such as exosomes, polymersomes, and protein-based nanoparticles investigated for possible applications in nanomedicine. Since the retention is highly variable the effectively applied dose cannot be determined by applying a simple syringe retention factor. The present work shall alert to the problem and illustrate its possible magnitude and unpredictable variability. As mitigation strategy adequate checks with different syringe types are proposed in order to find out whether a given combination of syringe type and nanoparticle suspension is affected by nanoparticle retention and, if necessary, to select a different syringe type that minimizes retention.